PRACTICE OF USING CHONDROPROTECTORS AND VITAMIN AND MINERAL MEDICATIONS IN THE TREATMENT OF ADOLESCENTS WITH BACKBONE OSTEOCHONDROPATHY AND SCOLIOSIS - V.V. Zhernokleeva; A.A. Togidny; A.F. Neretina; T.P. Korableva (Union of pediatricians of Russia, 2010)
The article describes the pressing issue, backbone scoliosis and osteochondropathy in adolescents. The authors justify the need to use chondroprotectors and replenishment of vitamins and minerals shortages in a comprehensive therapy for backbone pathology. Key words: backbone osteochondropathy, scoliosis, chondroprotectors, vitamins, minerals, adolescents. (Pediatric Pharmacology. - 2010; 7(2):96-101)